(Why) do central banks care about their profits? - Goncharov, I; Ioannidou, V; Schmalz, MC (Wiley, 2023)
We document that central banks are discontinuously more likely to report slightly positive profits than slightly negative profits, especially when political pressure is greater, the public is more receptive to extreme political views, and central bank governors are eligible for reappointment. The propensity to report small profits over small losses is correlated with higher inflation and lower interest rates. We conclude that there are agency problems at central banks, which give rise to discontinuous profit incentives that correlate with central banks’ policy choices and outcomes. These findings inform the debate about the political economy of central banking and central bank design.